Discrimination of holograms and real objects by pigeons (Columba livia) and humans (Homo sapiens). - Stephan, Claudia; Steurer, Michael Morten; Aust, Ulrike (Journal of Comparative Psychology, 2014)
The type of stimulus material employed in visual tasks is crucial to all comparative cognition research that involves object recognition. There is considerable controversy about the use of 2-dimensional stimuli and the impact that the lack of the 3rd dimension (i.e., depth) may have on animals’ performance in tests for their visual and cognitive abilities. We report evidence of discrimination learning using a completely novel type of stimuli, namely, holograms. Like real objects, holograms provide full 3-dimensional shape information but they also offer many possibilities for systematically modifying the appearance of a stimulus. Hence, they provide a promising means for investigating visual perception and cognition of different species in a comparative way. We trained pigeons and humans to discriminate either between 2 real objects or between holograms of the same 2 objects, and we subsequently tested both species for the transfer of discrimination to the other presentation mode. The lack of any decrements in accuracy suggests that real objects and holograms were perceived as equivalent in both species and shows the general appropriateness of holograms as stimuli in visual tasks. A follow-up experiment involving the presentation of novel views of the training objects and holograms revealed some interspecies differences in rotational invariance, thereby confirming and extending the results of previous studies. Taken together, these results suggest that holograms may not only provide a promising tool for investigating yet unexplored issues, but their use may also lead to novel insights into some crucial aspects of comparative visual perception and categorization. (PsycINFO Database Record (c) 2016 APA, all rights reserved)<br